INFORMATION SYSTEMS DEVELOPMENT AND TECHNOLOGY PLAN FOR TEA BARREL (PANABO BRANCH) - Reyna M. Bucio,; Joan A. Bravo,; Cris Dave A. Embodo,; Jobert R. Icalina ,; Florence Mae P. Langamon ,; Glendell R. Jadraque, (International Journal of Innovations in Engineering Research and Technology, 2022)
The food and beverage industry are not easy to invest in. When it comes to safeguarding the safety of people, the process of the company and all the possible outcomes are heavy load to think of. It is impossible to escape the difficulties and problems that any owner might have in a company, particularly pioneering entrepreneurs. Nonetheless, one of the best ways to find a solution is to propose viable coping mechanisms for those difficulties and problems that could make a significant contribution to the expansion and development of both its profits and the company. Most of the issues that organizations confront are related to the inventory management systems, resulting in various unfavorable conditions, including a scarcity of products. As a result, the researchers proposed a solution that consists of a system as well as the necessary platforms to solve the problems and ensure the business's fruitful and prosperous future.